Development of Student Worksheets Based on a Scientific Approach using the Group Investigation Model - soewarno warno; Siti Rahmah; Ngadimin Ngadimin; Abdul Halim (Asian Journal of Science Education, 2020)
This study aims to obtain student worksheets based on a scientific approach using the group investigation model that is feasible to apply to collision topic in High School. The research model used in this study refers to the ADDIE development model, namely: 1) Analysis, 2) Design, 3) Development, 4) Implementation and 5) Evaluation. The feasibility of student’s worksheets (SW) is measured by the results of SW validation, student learning outcomes and student response questionnaires. The SW is assessed by a team of experts. The overall results of the SW validation showed an average score of 4 was included in the good category. After the implementation of SW the learning outcomes have increased, namely the overall average of students is in the medium category and the average result of the overall response of students shows a score of 4 which is included in the agreed category Based on the three measurements of the feasibility of the SW, it shows that the SW is feasible to be applied in learning.